2019
DOI: 10.1002/hpm.2797
|View full text |Cite
|
Sign up to set email alerts
|

Nonattendance rates of scheduled outpatient appointments in a university general hospital

Abstract: Summary Objective We aimed to estimate nonattendance to scheduled medical ambulatory appointments rates globally and by subgroups. Design and participants We designed a retrospective cohort of all adult outpatients over 18 years old who requested at least one scheduled ambulatory medical appointment from 1 January 2015 to 31 December 2016. Setting Hospital Italiano de Buenos Aires is a university general hospital in the Autonomous City of Buenos Aires, Argentina. It includes an integrated health care network t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…As reported in many previous publications, nonattendance is very common in outpatient scheduled appointments. In this vein, we found a global nonattendance rate of 27.84% (95%CI 27.79‐27.9) in our center, where the nonattendance rate of general practitioner appointments was 25.53% (95%CI 25.42‐25.63) and that of clinical specialties, 27.78% (95%CI 27.68‐27.87) . The estimated nonattendance rate in the present study was lower for appointments with general practitioners.…”
Section: Discussionsupporting
confidence: 43%
“…As reported in many previous publications, nonattendance is very common in outpatient scheduled appointments. In this vein, we found a global nonattendance rate of 27.84% (95%CI 27.79‐27.9) in our center, where the nonattendance rate of general practitioner appointments was 25.53% (95%CI 25.42‐25.63) and that of clinical specialties, 27.78% (95%CI 27.68‐27.87) . The estimated nonattendance rate in the present study was lower for appointments with general practitioners.…”
Section: Discussionsupporting
confidence: 43%
“…5 A missed hospital appointment affects work flow, reduces patient and staff satisfaction and can lead to a loss in revenue as well as having a negative impact on patient’s health. 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 A missed hospital appointment affects work flow, reduces patient and staff satisfaction and can lead to a loss in revenue as well as having a negative impact on patient's health. 6 Several studies have explored the reasons for a missed hospital appointment. Some patient-related reasons include forgetting, being confused about the appointment date and time, not receiving an appointment reminder, not having transportation to attend, work or family commitments, feeling unwell or being admitted to the hospital on the same day of the appointment.…”
Section: Introductionmentioning
confidence: 99%
“…Although the response to conservative treatment has been reported as successful for pain reduction and improvement on function 46 , one of the main limitations of the study is the substantial number of patients failed to show up to follow-up visits, either after initial consultation or posterior to a trigger point injection, situation which could compromise the prognosis of their condition. Published data on attendance to appointments shows that nonattendance is a frequent problem affecting the ambulatory medicine system 47 . It has been shown that a reminder system that includes automatic phone calls or text messages can increase patient attendance.…”
Section: Discussionmentioning
confidence: 99%